2019
DOI: 10.1021/acs.chemrestox.9b00399
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Antioxidant Response by the Transcription Factor NRF2 Increases Bioactivation of the Mutagenic Air Pollutant 3-Nitrobenzanthrone in Human Lung Cells

Abstract: 3-Nitrobenzanthrone (3-NBA) is a suspected human carcinogen present in diesel exhaust. It requires metabolic activation via nitroreduction in order to form DNA adducts and promote mutagenesis. We have determined that human aldo-keto reductases (AKR1C1−1C3) and NAD(P)-H:quinone oxidoreductase 1 (NQO1) contribute equally to the nitroreduction of 3-NBA in lung epithelial cell lines and collectively represent 50% of the nitroreductase activity. The genes encoding these enzymes are induced by the transcription fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 51 publications
(108 reference statements)
4
20
0
Order By: Relevance
“…NRF2 is sequestered from the cytosol by KEAP1 where it is targeted for ubiquitination and proteasomal degradation by a Culin3 containing ubiquitin ligase E3 complex. , Upon activation by electrophiles or ROS, KEAP1 cysteines are modified leading to the release of NRF2 which can escape ubiquitination and translocate to the nucleus, where it binds with its heterodimeric partner small-maf on antioxidant response elements (AREs) in the promoter regions of responsive genes to cause new gene transcription. , Human genes regulated by AREs that display NTR activity include NQO1, AKR1C1, AKR1C2, AKR1C3 and XO , which implies that this stress response system may enhance nitroreduction. This was demonstrated in the case of 3-NBA where heterozygous ( NRF2 +/−) and homozygous ( NRF2 –/−) A549 cells were treated with the nitroarene. A549 cells constitutively express NRF2 and showed a high level of conversion of 3-NBA to 3-ABA that was reduced in the heterozygous cells and abolished in the homozygous knock down cells; similar results were obtained with 1-NP . These data suggest that the KEAP1-NRF2 pathway may induce bioactivation of the nitro group on a variety of xenobiotics.…”
Section: Gene Regulationsupporting
confidence: 56%
“…NRF2 is sequestered from the cytosol by KEAP1 where it is targeted for ubiquitination and proteasomal degradation by a Culin3 containing ubiquitin ligase E3 complex. , Upon activation by electrophiles or ROS, KEAP1 cysteines are modified leading to the release of NRF2 which can escape ubiquitination and translocate to the nucleus, where it binds with its heterodimeric partner small-maf on antioxidant response elements (AREs) in the promoter regions of responsive genes to cause new gene transcription. , Human genes regulated by AREs that display NTR activity include NQO1, AKR1C1, AKR1C2, AKR1C3 and XO , which implies that this stress response system may enhance nitroreduction. This was demonstrated in the case of 3-NBA where heterozygous ( NRF2 +/−) and homozygous ( NRF2 –/−) A549 cells were treated with the nitroarene. A549 cells constitutively express NRF2 and showed a high level of conversion of 3-NBA to 3-ABA that was reduced in the heterozygous cells and abolished in the homozygous knock down cells; similar results were obtained with 1-NP . These data suggest that the KEAP1-NRF2 pathway may induce bioactivation of the nitro group on a variety of xenobiotics.…”
Section: Gene Regulationsupporting
confidence: 56%
“…Furthermore, this transcriptomic and proteomic analysis showed that these genes were the most highly regulated by the NRF2-KEAP1 pathway (Agyeman et al, 2012). Recent CRISPR/Cas9 gene editing of NFE2L2 in A549 lung adenocarcinoma cells showed that high constitutive expression of AKR1C1, (Murray et al, 2019b). In A549 cells, KEAP1 is hypermethylated and mutated, leading to high levels of NRF2 (Wang et al, 2008;Fabrizio et al, 2019).…”
Section: Stress Response and Nuclear Factor-erythroid 2 P45-related Factor 2 Induction Ofmentioning
confidence: 82%
“…Nrf2 is highly pleiotropic, with many functions in biological processes like inflammation, lipid and xenobiotic metabolism and DNA repair, in addition to the central role it plays in cancer [ 27 , 28 , 61 , 62 ]. While Nrf2 is widely studied in the context of its protective activities, there is also a dark side including upregulation in cancer cells, where it can confer cytoprotection from chemotherapeutics, and in mutagenesis where genes upregulated by Nrf2 can lead to increased bioactivation of pro-carcinogens [ [62] , [63] , [64] ]. This underscores the need to better characterize the functions of Nrf2 during development.…”
Section: Discussionmentioning
confidence: 99%